2019
DOI: 10.1039/c9nj02199j
|View full text |Cite|
|
Sign up to set email alerts
|

Immobilization of quaternized polymers on bacterial cellulose by different grafting techniques

Abstract: Different polymers were immobilized on bacterial cellulose surfaces using grafting techniques to improve their mechanical properties and surface hydrophobicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…After VPI exposure, a new broad peak at a higher wavenumber can be observed. This change has been attributed to the quaternization and protonation of pyridine, 29,71,73 which correlates with the observations made from the photoemission analysis that that PVP is undergoing quaternisation and protonation when exposed to the TMA VPI process.…”
Section: Ga-ftirsupporting
confidence: 82%
See 2 more Smart Citations
“…After VPI exposure, a new broad peak at a higher wavenumber can be observed. This change has been attributed to the quaternization and protonation of pyridine, 29,71,73 which correlates with the observations made from the photoemission analysis that that PVP is undergoing quaternisation and protonation when exposed to the TMA VPI process.…”
Section: Ga-ftirsupporting
confidence: 82%
“…C=C stretching vibrations (attributed to the pyridine ring) are observed at 1726 cm -1 and pyridine associated stretching modes at 1600 cm -1 . 29,[71][72][73] Peaks at 1416 cm -1 and 1232 cm 1 are associated with C-H deformation vibrations.…”
Section: Ga-ftirmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to cellulose’s high abundance, biodegradability, and biocompatibility, the field of research on its modification has attained greater recognition during the recent decades. , Plant cellulose is predominantly present in nature; however, it possesses several drawbacks such as contamination with lignin, wax, and hemicellulose . On the other hand, bacterial cellulose emphasizes many merits over plant cellulose, such as high purity (free of impurities such as lignin and wax), biocompatibility, water retention capacity, crystallinity, degree of polymerization, surface area, mechanical properties (flexibility and tensile strength), and biodegradability. Furthermore, bacterial cellulose pellicles can be produced effectively through the fermentation process of a bacterial strain at a low cost in an environmentally friendly manner. , As a consequence of its several merits, it emerged as a promising candidate for various applications through successive surface modifications including both covalent and noncovalent approaches. , Various synthetic methodologies have been executed on either plant cellulose or bacterial cellulose, which included silylation, acylations, aminylation, acetylation, carboxymethylation, and incorporation of nanoparticles or polymeric materials to enhance the properties of cellulose. , A generic methodology to apply on the cellulose of different sources is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Our group recently reported the modification of bacterial cellulose by covalent or noncovalent approaches, . In another work, Fernandes et al reported aminoalkyl-grafted BC materials through a silane anchoring group which showed antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%